“PSYCHOLOGICAL DESTABILIZATION THROUGH CONTINGENCY: THE CASE OF REMARQUE’S ANTIWAR NOVELS” (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article investigates the psychological destabilization of characters in Erich Maria Remarque’s antiwar novels as a result of contingent, unpredictable events. Drawing on concepts from trauma theory, existentialism, and literary psychology, the study explores how the breakdown of order and the randomness of wartime experiences contribute to a fragmented sense of identity and emotional disintegration in Remarque’s protagonists. Through textual analysis of All Quiet on the Western Front and The Road Back, the article reveals that contingency operates not merely as a narrative device but as a destabilizing existential force. These contingent experiences expose the fragility of the human psyche and deepen the antiwar message of Remarque’s fiction.